2014
DOI: 10.2196/jmir.3722
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Electronic Patient Portal Among the Chronically Ill: An Observational Study

Abstract: BackgroundElectronic patient portals may enhance effective interaction between the patient and the health care provider. To grasp the full potential of patient portals, health care providers need more knowledge on which patient groups prefer electronic services and how patients should be served through this channel.ObjectiveThe objective of this study was to assess how chronically ill patients’ state of health, comorbidities, and previous care are associated with their adoption and use of a patient portal.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Number of internet/ email devices 1 73 1 89 : Hypertension, hyperlipidemia, cerebrovascular disease, peripheral vascular disease, chronic kidney disease stage, nephrolithiasis (no) 94 : having depression 100 : Psychiatric history 102 : bipolar disorder 107 : Hepatitis C, depression (+ve), hepatitis B (no) 108 : Type 1 or 2 diabetes, hypercholesterolemia (no) 110 : Diabetes or elevated lipids 113 : Type 1 Diabetes 114 : Type of diabetes 115 : Chronic diseases, or cancer 118 : HIV, hyperlipidemia, hypertension, posttraumatic stress disorder, traumatic brain injury, spinal cord injury, depression and anxiety (+ve) complex chronic medical conditions (CHD, CHF, Schizophrenia) (-ve) 128 :…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Number of internet/ email devices 1 73 1 89 : Hypertension, hyperlipidemia, cerebrovascular disease, peripheral vascular disease, chronic kidney disease stage, nephrolithiasis (no) 94 : having depression 100 : Psychiatric history 102 : bipolar disorder 107 : Hepatitis C, depression (+ve), hepatitis B (no) 108 : Type 1 or 2 diabetes, hypercholesterolemia (no) 110 : Diabetes or elevated lipids 113 : Type 1 Diabetes 114 : Type of diabetes 115 : Chronic diseases, or cancer 118 : HIV, hyperlipidemia, hypertension, posttraumatic stress disorder, traumatic brain injury, spinal cord injury, depression and anxiety (+ve) complex chronic medical conditions (CHD, CHF, Schizophrenia) (-ve) 128 :…”
mentioning
confidence: 99%
“…Visual acuity 1 100 1 Risk factor for HIV (gay) 1 107 1 Having kidney transplant 1 89 1 Length of membership in the healthcare setting 1 81 Health plan duration 1 107 1 Dipstick proteinuria (≥1+) 1 89 1 Serum creatinine level 1 89 1 Having ≥1 HbA1C measurement 1 108 1…”
mentioning
confidence: 99%
“…A previous study published on this topic found that the portal had the greatest effect on activation among patients starting at the highest level of patient activation [ 18 ]. It has also been reported previously [ 47 ] that previous care received by the patient, rather than state of health, age, gender, or patient activation, is an important factor predicting the attractiveness of electronic patient portal use. Among patients with similar disease burden, those who chose not to use the portal had received more services from primary care in the previous year than those who had used the portal [ 47 ].…”
Section: Discussionmentioning
confidence: 64%
“…Articles reporting on portals with a medium number of functionalities (five to eight) differentiated between outcomes on design and development of a patient portal [26,28,29,30], positive effects on health-related issues [31,32] or creating awareness and self-management among patients [33,34,35]. Surprisingly, the group of articles with the fewest items (three to four) on the Minkman model are studies that focus primarily on care coordination [36,37,38,39,40,41,42,43].…”
Section: Study Outcomementioning
confidence: 99%